Replacing Soybean Meal with Hemp Leaves in a Dairy Cow Diet: Plasma Antioxidative Capacity, Inflammatory Parameters and Milk Constituents - Jessica Schwerdtfeger; Solvig Görs; Dirk Dannenberger; Björn Kuhla (Animals)
Hemp is rich in bioactive compounds known to exert antioxidant and anti-inflammatory properties. We hypothesised that feeding industrial hemp leaves would increase the antioxidative capacity, reduce pro-inflammatory markers, and modulate the milk amino and fatty acid profiles of dairy cows. Twelve Holstein dairy cows were randomly assigned to a total mixed ration (TMR) containing 7.4% industrial hemp leaves (HEMP) of the Santhica 27 variety or a TMR-based diet containing 3.5% soybean meal (CON). Diets were fed in a cross-over design, each for 2 weeks divided by a 2-week washout period. HEMP cows revealed higher plasma and milk cannabinoid concentrations, plasma antioxidative capacity and anserine concentration, but lower plasma π-methylhistidine, α-aminoadipic acid and isoleucine concentrations. Lipid peroxidation and tumour necrosis factor-alpha concentrations were not different between groups. The leukocyte RELA mRNA expression was higher, whereas the TNFA mRNA abundance tended to be lower in the HEMP group. In milk, n-3 polyunsaturated fatty acid (PUFA) concentrations were higher, and the n-6/n-3 PUFA ratio was lower in HEMP than in CON cows. The results provide evidence that the supplementation with Santhica 27 hemp leaves increases the antioxidative capacity of dairy cows and results in a transfer of cannabinoids into milk.